Improvement of Teaching Materials of Microeconomic Theory (Case Study of Economic Education Study Program in State University of Medan) - Putri Sari MJ Silaban; Joko Suharianto; Aurora Elise Putriku; Sabda Dian Nurani Siahaan (Budapest International Research and Critics University, 2021)
This study aims to produce microeconomic theory teaching materials. This study uses a research and development (R&D) method based on the Bord and Gall concept. The population of this study was all students of microeconomic theory subjects in the economic education study program in 2020. The sample was determined by purposive random sampling and the sample class was used for application and limited testing of a small sample, namely class C of Economic Education. Based on the results of the study, the microeconomic theory teaching materials made and validated by 3 expert validators resulted in a decision that teaching materials had a very high level of feasibility (81.25%) with a note that revisions needed to be made. After all revision notes have been corrected, a small group trial was conducted on 20 class C students of economic education in the microeconomic theory course. Based on the results of small group trials, it is known that there has been a significant increase in learning outcomes before and after using Microeconomic Theory teaching materials. The result is that all factors of convenience for users, usability, and time effectiveness have a percentage value of 81.85%, meaning that it is concluded that the book developed has met the criteria for readability and practicality. This research was conducted only up to the 7th stage, namely producing a revised draft of the teaching material product. The result is that all factors of convenience for users, usability, and time effectiveness have a percentage value of 81.85%, meaning that it is concluded that the book developed has met the criteria for readability and practicality. This research was conducted only up to the 7th stage, namely producing a revised draft of the teaching material product. The result is that all factors of convenience for users, usability, and time effectiveness have a percentage value of 81.85%, meaning that it is concluded that the book developed has met the criteria for readability and practicality. This research was conducted only up to the 7th stage, namely producing a revised draft of the teaching material product.